Empathetic communication in higher education: Implications for teacher success - Bartra-Rivero, Karina Raquel (2025)
This study examines the relationship between teachers' empathetic communication and their academic performance, focusing on two dimensions: empathetic concern and perspective taking. The main objective was to determine if there is a positive and significant relationship between empathetic communication and teaching performance in the university context. A descriptive correlational design was employed to analyze data collected from 364 students from private universities in Lima. Twenty-four items of empathetic communication and 23 of teaching performance were evaluated using a Likert scale survey. As a result, Spearman correlation analyses revealed a positive and significant correlation between empathetic communication and teaching performance (r = 0.211, P < 0.01). Furthermore, positive, and significant correlations were found between empathetic concern (r = 0.279, P < 0.01) and perspective taking (r = 0.166, P < 0.01) with teaching performance. It is concluded that empathetic communication is positively associated with teaching performance, highlighting the importance of developing empathetic communication skills in teachers to enhance their effectiveness in the classroom. However, caution is advised to balance empathy to avoid potential biases or deviations in teaching. It is recommended to focus teacher training programs on strengthening these social skills to optimize the teaching learning process.